Optimization of Ship Cargo Operations by Genetic Algorithm - Hess, Svjetlana; Hess, Mirano (Promet - Traffic&Transportation, 2012)
This paper addresses the optimization possibilities of cargo operations onboard ship in order to minimize the operational costs through optimal structure of resources required. Since the setup model consists of composite objective function with several decision variables whose solution is constrained in the field Z+, the method for direct finding of optimal solution does not lead to satisfactory results. Therefore, for the solution of the problem a genetic algorithm has been developed, which yields an acceptable solution in a short time. In the given area of the possible solutions, the genetic algorithm, with variations of different crossover methods and mutation rates, gives a solution that coincides with the observed and expected results when operations of loading/unloading of general cargo ship are concerned. With the obtained structure of resources allocated in cargo operations, the minimum of operational costs is reached. KEY WORDS: ship, cargo operations, optimization, genetic algorithm